1939
DOI: 10.1042/bj0330128
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of carbohydrate metabolism to protein metabolism

Abstract: EARLIER observations showed that the provision of excess of energy in the human diet is attended by a storage of N and S, the storage being more marked when the surfeit is in the form of carbohydrate than when in the form of fat [Cuthbertson & Munro, 1937]. Simultaneously with these observations, it was demonstrated by Larson & Chaikoff [1937] in one-day superimposition experiments on dogs, that this storage was only provoked by carbohydrate ingested within 4 hr. before or after the protein meal. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1946
1946
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…; in either case the growth was inferior to that observed when the same proportion of the amino acid was incorporated in the diet. More recently, Elman(i5) obtained similar results with dogs, while Cuthbertson and his colleagues (16,17) found that when the protein and carbohydrate fractions of a diet, jointly capable of maintaining nitrogen equilibrium, were given at different times of the day to human adults (16) or adult rats(i7) the nitrogen balance became negative and there was loss of body weight.…”
mentioning
confidence: 92%
“…; in either case the growth was inferior to that observed when the same proportion of the amino acid was incorporated in the diet. More recently, Elman(i5) obtained similar results with dogs, while Cuthbertson and his colleagues (16,17) found that when the protein and carbohydrate fractions of a diet, jointly capable of maintaining nitrogen equilibrium, were given at different times of the day to human adults (16) or adult rats(i7) the nitrogen balance became negative and there was loss of body weight.…”
mentioning
confidence: 92%
“…T h e presence of carbohydrate in a meal can also influence the subsequent metabolic fate of the amino acids after absorption. Some years ago we noted that nitrogen balance underwent a temporary deterioration when the protein and carbohydrate in a diet were consumed in separate meals, whereas no such change in nitrogen balance followed separation of dietary protein and fat (Cuthbertson & Munro, 1939;Munro, 1949). Subsequent studies (Munro, Black & Thomson, 1959) suggest that the presence of carbohydrate in a meal causes release of insulin which then induces deposition of some of the incoming amino acids in muscle in the form of labile protein.…”
mentioning
confidence: 99%